Antigen‐driven CD4+ T‐cell anergy: a pathway to peripheral T regulatory cells. Issue 3 (4th December 2020) - Eggenhuizen, Peter J; Ng, Boaz H; Ooi, Joshua D
Abstract : In their recent publication, Kuczma and colleagues have provided evidence that advances the relationship between naive T cells, T cell anergy and T regulatory cells. Their findings strengthen the understanding of how these T cell subsets function in relation to self and microbiota‐derived epitopes to promote and maintain peripheral tolerance to self and mucosal antigens.